Foundation Phase teachers' responses to curriculum change in South Africa over the past two decades: a case study of two schools - Nakaonga, Ruth (Rhodes University, Faculty of Education, Department of Education, 2014)
South Africa has experienced three significant curriculum reforms since 1994. The first of these replaced the 'apartheid' curriculum with C2005 based largely on Outcomes Based Education. In the second stage C2005 gave way to the National Curriculum Statements, a simplified version of C2005. Finally, the NCS was replaced with CAPS. This research study investigates the perceptions, attitudes and experiences of teachers implementing these curriculum changes. It focuses in particular on Foundation Phase in 2012, the year in which CAPS was implemented in that phase. It took the form of an interpretive case study, using qualitative data generating and analysis techniques. Principals and selected teachers of two primary schools in Grahamstown "“ an ex-Model C school and a performing 'township' school - were the respondents of the study. Data were generated chiefly through questionnaires and semi-structured interviews, supplemented by document analysis and observation. The findings revealed that the teachers in this study are frustrated and angry about the frequency of curriculum change in South Africa. Respondents are particularly critical of OBE and the NCS. While they welcome the need for a departure from 'apartheid' curricula, they feel the pedagogical underpinning of the NCS "“ with its emphasis on learner-centredness "“ disempowered them as teachers. Hence, they welcomed CAPS which seems to return to content "“ rather than skills and attitudes "“ and re-instates the teacher as the chief giver of knowledge and manager of learning.
Keywords: Curriculum change -- South Africa; Educational change -- South Africa; Education, Primary -- South Africa; Teachers -- South Africa -- Attitudes